A case study of an ESL Student learning English in an English Speaking Country: Studi kasus seorang Siswa ESL yang belajar bahasa Inggris di Negara Berbahasa Inggris - Taufiq, Wahyu (Universitas Muhammadiyah Sidoarjo, 2016)
Different students who learn English as the second language has various problems and strategies to overcome. A case study on an international student who learns English as a second language in an English speaking country raised some problems he had and offered some strategies he used during the process of learning. The progress of learning from the first time coming and studying at a college in Australia was mainly the core data collected on this study. The data copes from his formal academic learning experience and also from informal situation that he met at his everyday life. This study applied qualitative research method and use interview and recording as the instruments. The data were analized through three stages: data reduction, data display, and conclusion drawing. The results of the study show that the learner experiences a range of English learning problems which happened after his coming to Australia and some strategies he used to overcome.